Evaluation of PET Degradation Using Artificial Microbial Consortia - Qi, Xinhua; Ma, Yuan; Chang, Hanchen; Li, Bingzhi; Ding, Mingzhu; Yuan, Yingjin (Frontiers in Microbiology, 2021)
Polyethylene terephthalate (PET) biodegradation is regarded as an environmentally friendly degradation method. In this study, an artificial microbial consortium composed of Rhodococcus jostii, Pseudomonas putida and two metabolically engineered Bacillus subtilis was constructed to degrade PET. First, a two-species microbial consortium was constructed with two engineered B. subtilis that could secrete PET hydrolase (PETase) and monohydroxyethyl terephthalate hydrolase (MHETase), respectively; it could degrade 13.6% (weight loss) of the PET film within seven days. A three-species microbial consortium was further obtained by adding R. jostii to reduce the inhibition caused by terephthalic acid (TPA), a breakdown product of PET. The weight of PET film was reduced by 31.2% within seven days, achieving about 17.6% improvement compared with the two-species microbial consortium. Finally, P. putida was introduced to reduce the inhibition caused by ethylene glycol (EG), another breakdown product of PET, obtaining a four-species microbial consortium. With the four-species consortium, the weight loss of PET film reached 23.2% under ambient temperature. This study constructed and evaluated the artificial microbial consortia in PET degradation, which demonstrated the great potential of artificial microbial consortia in the utilization of complex substrates, providing new insights for biodegradation of complex polymers.